Modulation of myeloid-derived suppressor cell functions by oral inflammatory diseases and important oral pathogens - García-Arévalo, Fernando; Leija-Montoya, Ana Gabriela; González-Ramírez, Javier; Isiordia-Espinoza, Mario; Serafín-Higuera, Idanya; Fuchen-Ramos, Dulce Martha; Vazquez-Jimenez, J. Gustavo; Serafín-Higuera, Nicolas (Frontiers in Immunology, 2024)
The oral cavity presents a diverse microbiota in a dynamic balance with the host. Disruption of the microbial community can promote dysregulation of local immune response which could generate oral diseases. Additionally, alterations in host immune system can result in inflammatory disorders. Different microorganisms have been associated with establishment and progression of the oral diseases. Oral cavity pathogens/diseases can modulate components of the inflammatory response. Myeloid-derived suppressor cells (MDSCs) own immunoregulatory functions and have been involved in different inflammatory conditions such as infectious processes, autoimmune diseases, and cancer. The aim of this review is to provide a comprehensive overview of generation, phenotypes, and biological functions of the MDSCs in oral inflammatory diseases. Also, it is addressed the biological aspects of MDSCs in presence of major oral pathogens. MDSCs have been mainly analyzed in periodontal disease and Sjögren's syndrome and could be involved in the outcome of these diseases. Studies including the participation of MDSCs in other important oral diseases are very scarce. Major oral bacterial and fungal pathogens can modulate expansion, subpopulations, recruitment, metabolism, immunosuppressive activity and osteoclastogenic potential of MDSCs. Moreover, MDSC plasticity is exhibited in presence of oral inflammatory diseases/oral pathogens and appears to be relevant in the disease progression and potentially useful in the searching of possible treatments. Further analyses of MDSCs in oral cavity context could allow to understand the contribution of these cells in the finetuned balance between host immune system and microorganism of the oral biofilm, as well as their involvement in the development of oral diseases when this balance is altered.